Toward harmonization of aging and technology research: German adaptation of the mobile device proficiency questionnaire (MDPQ) for older adults - Schlomann, Anna; Wahl, Hans-Werner; Schmidt, Laura; Memmer, Nicole; Rietz, Christian; Charness, Neil H.; Boot, Walter Richard (European journal of ageing, 2024)
The Mobile Device Proficiency Questionnaire (MDPQ) is a well-established, reliable, and valid instrument to measure basic and advanced mobile device skills among older adults. We offer a German adaptation of the MDPQ and report reliability and validity findings. A controlled translation procedure was applied. The translated scale was tested in two analytical samples with an age range of 50-95 years in 2020 (n = 548) and 2022 (n = 276). To assess reliabilities, internal consistencies and test-retest reliabilities are reported. To assess validity, we analyze the scale in the context of gender, age, and educational differences and its associations with measures of technology use and attitudes towards technology (convergent and divergent validity). The German adaptation of the MDPQ was found to be reliable and valid as the original version. The scale demonstrated an excellent internal consistency in both studies with α = 0.95 (study 2: α = 0.92) and ω = 0.95 (study 2: ω = 0.93). Subscale internal consistencies were all ≥ 0.65. Test-retest reliabilities with measurement waves 2 years apart showed excellent values (MDPQ full scale: rtt = 0.84, p < 0.001). We also found the expected factorial structure of the scale, positive associations with education, mobile device use and technology attitudes, and negative associations with age. Women scored lower than men. The German adaptation of the MDPQ can serve as a useful tool to estimate mobile device skills in older adults in German speaking countries in a reliable and valid way, for example in survey research, research projects, and practice contexts. Translating and implementing the MDPQ in other European countries will help to further strengthen internationally harmonized assessments in technology and aging research.
Gesehen am 17.06.2025